The role of the Arabic language and diverse nationalities in creating a positive environment, strengthening human behavior, and supporting a good community. - Ratnadewiati, Zabrina Aprillia; Aulia, Dien; As-Sabt, Jalaluddin; Mustofa, Saiful (Journal of Arabic Education and Linguistic, 2025)
Social phenomena in the world of education demonstrate that learning Arabic not only serves as a means of religious communication but also plays a significant role in shaping a positive learning environment, fostering positive behavior, and supporting the development of a character-based society. In Islamic educational settings, Arabic becomes a vehicle for instilling moral, spiritual, and social values ​​that align with the vision of religious schools and the student profile in Banchalasia. This study aims to analyze the role of Arabic language learning in creating a positive environment, promoting ethics, and contributing to the development of national character. The study employs a qualitative descriptive approach using library research methods. Data was obtained from primary sources such as textbooks, learning units, educational documents, and scholarly articles, as well as secondary sources such as journals, transcripts, and previous studies. Data collection techniques were implemented through documentation studies, followed by content analysis techniques involving summarization, presentation, and conclusion drawing. This study demonstrates that learning Arabic significantly contributes to building a character-based school environment, which is reflected in the school's vision and mission of developing noble character and enhancing the student profile in Banchalasia. Learning Arabic also contributes to shaping students' character through the use of polite conversation and idiomatic expression exercises that enhance precision. These findings align with previous research that portrays Arabic as a vehicle for cultivating noble morals and Islamic character. Furthermore, learning Arabic supports students' participation in global networks, including through the ASEAN-Middle East Business Forum and educational cooperation between Indonesia and Saudi Arabia. Overall, Arabic forms a crucial foundation for building a generation with a strong character and a global perspective, contributing to the development of a dignified nation..